Analisis Terhadap Tindak Pidana Pemerasan (Studi Kasus Putusan PNTK Nomor: 560/Pid/B/2011/PN.TK) - . Kamilatun (Universitas Bandar Lampung (UBL), 2012)
Crime is a form of behavior that is contrary to human morals (immoral), harmful to society and break the law, the problem of evil is unavoidable and is always there, crime and insecurity cause public disorder, development to achieve the welfare of the community, one form of crime or crime is extortion, as in article 368 of the Criminal Code, it is necessary to police efforts to prevent and combat crime in accordance with the Law. 2 in 2002. The issue in this study are: a. whether the legal basis in criminal extortion by ruling case number: 560/Pid-B/2011/PN.TK, The results of this study concluded that: consideration of criminal law decision extortion case number: 560/Pid-B/2011/PN.TK is Article 368 paragraph (1) of the Criminal Code, the defendant's criminal extortion's. Anugra Imanudin, Hasan Basri and M. Hidayat sentenced to imprisonment for 6 months, factors that cause crime of personal and situational factors.